Influx of kynurenine into the brain is involved in the reduction of ethanol consumption induced by Ro 61‐8048 after chronic intermittent ethanol in mice. (7th March 2022) - Gil de Biedma‐Elduayen, Leticia; Giménez‐Gómez, Pablo; Morales‐Puerto, Nuria; Vidal, Rebeca; Núñez‐de la Calle, Carlos; Gutiérrez‐López, María Dolores; O'Shea, Esther; Colado, María Isabel
Abstract : Background and Purpose: The kynurenine pathway has been proposed as a target for modulating drug abuse. We previously demonstrated that inhibition of kynurenine 3‐monooxygenase (KMO), using Ro 61‐8048, reduces ethanol consumption in a binge drinking model. Here, we investigate the effect of the kynurenine pathway modulation in ethanol‐dependent mice. Experimental Approach: Adult male and female mice were subjected to a Chronic Intermittent Ethanol (CIE) paradigm. On the last day of CIE, mice were treated with Ro 61‐8048, Ro 61‐8048 + PNU‐120596, a positive allosteric modulator of α7nAChR, and Ro 61‐8048 + L‐leucine or probenecid, which blocks the influx or efflux of kynurenine from the brain, respectively. Ethanol, water consumption and preference were measured and kynurenine levels in plasma and limbic forebrain were determined. Key Results: Ro 61‐8048 decreases consumption and preference for ethanol in both sexes exposed to the CIE model, an effect that was prevented by PNU‐120596. The Ro 61‐8048‐induced decrease in ethanol consumption depends on the influx of kynurenine into the brain. Conclusion and Implications: Inhibition of KMO reduces ethanol consumption and preference in both male and female mice subjected to CIE model by a mechanism involving α7nAChR. Moreover, this centrally‐mediated effect depends on the influx of peripheral kynurenine to the brain and can be prolonged by blocking the efflux of kynurenine from the brain. Here, for the first time, we demonstrate that the modulation of the kynurenine pathway is an effective strategy for the treatment of ethanol dependence in both sexes.